PHENOTYPIC AND FUNCTIONAL COMPARISON OF MOBILIZED PERIPHERAL BLOOD VERSUS UMBILICAL CORD BLOOD MEGAKARYOCYTE POPULATIONS - Kellner, Joshua (Cytotherapy, 2014)
BACKGROUND AIMS: Hematopoietic stem cell transplantation of mobilized peripheral blood progenitor cell (PBPC) products results in rapid platelet engraftment while use of cord blood (CB) shows significant delays. The difference in the quality and number of megakaryocyte (MK) progenitors that may be responsible for the delay in platelet engraftment has not been fully defined. The objective of this study was to quantitate the cells of the MK lineage in PBPC and CB products to determine if potential differences existed. METHODS: We examined PBPC or CB for differences in surface markers and subpopulations as well as polyploidization status within the MK lineage. Colony forming assays (CFU-MK) were used to determine if differences existed in the clonogenic MK progenitor cell. Finally, we transplanted PBPC and CB MNCs into NOD/SCID/IL2Rγ−/− (NSG) mice to study platelet engraftment rates. RESULTS: Equivalent MK populations and polyploidization was observed in PBPCs and CB. MK progenitors were present only in CD34+ cells and had little difference in colony growth between PBPC and CB. Additionally, MK subpopulations were similar in either product with a slightly more progenitor-enriched phenotype in CB. Finally, when PBPC or CB was transplanted at similar doses, equivalent platelet engraftment rates were observed. CONCLUSIONS: PBPC and CB contain similar frequencies of MK populations and when transplanted in comparable doses, CB is as effective as PBPCs in producing platelet engraftment in vivo. Understanding the differences in MK populations between PBPC and CB could help generate protocols to improve platelet engraftment after CB transplantation.